Hubungan Lama Hemodialisis Dengan Kejadian Pruritus Pada Pasien Yang Mengalami Gagal Ginjal Kronik Di RS. Ibnu Sina Makassar Periode 2024 - Zahra Rindu Tsabitha Alif; Dian Amelia Abdi; Andi Kartini Eka Yanti; Indah Lestari Daeng K; Darariani Iskandar (Wal'afiat Hospital Journal, 2025)
Chronic Kidney Disease (CKD) has become a global health problem and hemodialysis is one of the most widely used treatment therapies. Pruritus is one of the complications in hemodialysis patients. to determine the relationship between the duration of hemodialysis with the incidence of Pruritus in patients with chronic renal failure at Ibnu Sina Hospital Makassar period 2024. This study used an analytic observational method with cross sectional approach design. The population of all patients undergoing CKD who underwent hemodialysis amounted to 20 people. Data were analyzed by Kruskal-Wallis test. There is a significant relationship between the duration of hemodialysis with the incidence of Pruritus in CKD patients with a p value of 0.033. This value means p less than 0.05, which is then H1 is accepted. There is a significant relationship between duration of hemodialysis with the incidence of Pruritus in CKD patients at Ibnu Sina Hospital Makassar Period 2024.